ABHB Annual Bibliography of the History of the Printed Book and Libraries Volume 4: Publications of 1973 - Vervliet, Hendrik D. L.; SpringerLink (Online service) (Hague Martinus Nijhoff, 1975)
The history of printing, books, and libraries, is confined only to a limited extent within the boundaries of individual countries. There are, indeed, few historical developments which have played a more universal role, in reaction against all kinds of particularism, than type design, printing, book production, publishing, illustration, binding, librarianship, journal ism, and related subjects. Their history should be assessed and studied primarily in an international, not in a local, context. The bibliographical resources, however, which the historian of these sub jects has at his disposal correspond hardly at all to the essentially inter national character of the object of his studies. Since the appearance of the retrospective bibliography of BIG MORE and WYMAN, covering the subject comprehensively up to 1880, the only current bibliography has been the lnternatwnale Bibliographie des Buch-und Bi bliothekswesens. Covering a representative part of newly published liter ature, it appeared from 1928, but did not survive the Second World War. More recently, several useful, but limited, bibliographies have appeared.
A. General Works about the History of the Printed Book and Library -- General, 24; Bulgaria, 26; France, 26; Germany, 26; USSR, -- B. Paper, Inks, Printing Materials -- General, 27; France, 27; Germany, 28; Great Britain, 28; Hungary, 28; Italy, 28; Ireland, 29; Japan, 29; Mexico, 29; Poland, 29; Spain, 29; Switzerland, 29; USSR, -- C. Calligraphy, Type Design, Typefounding -- General, 29; Austria, 30; Belgium, 30; China, 31; France, 31; Germany, 31; Great Britain, 31; India, 32; Ireland, 32; Israel, 32; Italy, 32; Netherlands, 32; Spain, 32; Switzerland, 33; USA, -- D. Layout, Composing, Printing, Presses, Printed Books, Incl. Incunabula, ETC. -- General, 33; Austria, 38; Belgium, 38; Bulgaria, 41; Czechoslovakia, 41; Finland, 41; France, 41; Germany, 46; Great Britain, 51; Hungary, 57; India, 58; Ireland, 58; Italy, 58; Luxemburg, 60; Netherlands, 61; Poland, 61; Portugal, 62; Rumania, 62; Spain, 63; Switzerland, 63; USA, 64; USSR, 64; Vietnam, -- E. Book Illustration -- General, 65; Austria, 67; Belgium, 67; Bulgaria, 68; Czechoslovakia, 68; France, 68; Germany, 71; Great Britain, 73; Ireland, 74; Italy, 74; Netherlands, 75; Poland, 75; Portugal, 75; Switzerland, 76; USA, 77; USSR, -- F. Bookbinding -- General, 77; Austria, 78; Denmark, 78; France, 78; Germany, 78; Great Britain, 79; Ireland, 80; Italy, 80, Netherlands, 81; Poland, 81; Spain, 81; Switzerland, 81; USA, -- G. Book Trade, Publishing -- General, 81; Australia, 83; Austria, 83; Belgium, 83; Bulgaria, 83; Czechoslovakia, 83; Denmark, 83; France, 83; Germany, 86; Great Britain, 90; Israel, 93; Italy, 93; Japan, 93; Netherlands, 94; Poland, 94; Sweden, 95; Switzerland, 95; USA, 95; USSR, -- H. Bibliophily, Book-Collecting -- General, 98; Austria, 100; Belgium, 100; Czechoslovakia, 100; Finland, 100; France, 100; Germany, 103; Great Britain, 104; Hungary, 106; Ireland, 106; Italy, 106; Poland, 106; Rumania, 107; Switzerland, 107; USA, 107; USSR, -- J. Institutions, Libraries, Librarianship, Scholarship -- General, 108; Austria, 109; Belgium, 111; Bulgaria, 112; China, 112; Czechoslovakia, 112; Denmark, 112; France, 113; Germany, 115; Great Britain, 117; Hungary, 120; India, 121; Ireland, 121; Italy, 121; Netherlands, 122; Norway, 122; Poland, 122; South Africa, 125; Spain, 126; Sweden, 126; Switzerland, 126; USA, 127; USSR, 127; Yugoslavia, -- K. Legal, Economic, Social Aspects -- General, 129; Austria, 130; Belgium, 130; France, 130; Germany, 131; Great Britain, 132; Hungary, 133; Italy, 134; Netherlands, 134; Poland, 134; Switzerland, 134; USA, 134; USSR, -- L. Newspapers, Journalism -- General, 136; Australia, 136; Austria, 137; Belgium, 137; Denmark, 138, France, 138; Germany, 142; Great Britain, 143; Hungary, 144; Ireland, 145; Italy, 145; Madagascar, 146; Netherlands, 146; Norway, 146; Poland, 146; USA, 147; USSR, -- M. Secondary Subjects -- General, 149; Philosophy, psychology, 150; Religion, 150; Social Sciences, 154; Linguistics and literature, 159; English, 160; German, 167; Other Germanic languages, 168; French, 169; Italian, 174; Spanish, Portuguese, 175; Classical languages, 175; Slavonic and Baltic languages, 177; Other languages, 179; Mathematics and pure sciences, 180; Applied sciences, 182; Arts, entertainments, 184; Geography, 189; History, -- Index I. Author's Names and Anonyms -- Index II. Subject Index of Geographical and Personal Names.
Includes index.
Keywords: Publishers and publishing; Humanities / Arts / Design; Printing and Publishing